Potential of chitosan coating in delaying the postharvest anthracnose (Colletotrichum gloeosporioides Penz.) of Eksotika II papaya - Ali, Asgar; Tengku Muda Mohamed, Mahmud; Sijam, Kamaruzaman; Siddiqui, Yasmeen (Wiley Interscience, 2010)
The in vitro and in vivo fungicidal activity of chitosan was studied against Colletotrichum gloeosporioides, the causal agent of anthracnose in papaya fruits. Chitosan at 1.5% and 2.0% concentrations showed a fungistatic effect with 90–100% inhibition (significant at P ≤ 0.05) of the fungal mycelial growth. Changes in the conidial morphology were also observed with the higher chitosan concentrations after 7-h incubation. In vivo studies showed that 1.5% and 2.0% chitosan coatings on papaya not only controlled the fruit decay but also delayed the onset of disease symptoms by 3–4 weeks during 5 weeks storage at 12 ± 1°C and slowed down the subsequent disease development. However, when leaving the fruits to ripen at ambient temperature (28 ± 2°C), 2.0% chitosan was less effective than 1.5% in controlling the disease development. Chitosan coatings also delayed the ripening process by maintaining the firmness levels, soluble solids concentration and titratable acidity values during and after storage.